KINERJA PENGISIAN DOKUMEN REKAM MEDIS DI PUSKESMAS MADAPANGGA BIMA NTB - Syamsuriansyah Syamsuriansyah; Uswatun Hasanah; Reni Chairunnisa; Helmina Andriani; Nik Azliza Bt Arifin (Jurnal Kesehatan, 2021)
The percentage of incomplete filling of medical record documents at the Madapangga Health Center shows that the Minimum Service Standards in the Hospital are not yet 100%. Incomplete data has shown that the completeness of filling out medical record documents is still not up to the specified standard. The incompleteness of filling out the medical record document may be caused by the performance factor of the officer in filling out the medical record document for inpatients. The purpose of this study was to analyze the performance factors in filling out medical record documents for inpatients at the Madapangga Public Health Center. This study uses qualitative research that aims to identify and analyze the performance factors of filling out inpatient medical record documents at the Madapangga Health Center, which will be linked to performance theory with personal factors, leadership factors, team factors, system factors, and situational factors, and using the method USG (Urgency, Seriousness, Growth) to determine the main factors of the 5 factors that affect the performance, as well as efforts to fix problems using brainstorming. The results of this study obtained that the priority causes of the problem of incomplete filling of medical record documents for inpatients at the Madapangga Health Center were the lack of awareness of each individual regarding filling out medical record documents, lack of evaluation and monitoring, lack of socialization, lack of understanding related to SOPs for filling out medical record documents due to SOPs for filling out medical records. There is no medical record document yet, so the Puskesmas Madapangga asked the researchers to make an SOP for filling in inpatient record documents. As a suggestion, it is carried out to raise commitments for the completeness of filling out medical record documents, conducting socialization, evaluation and monitoring on a regular basis, as well as making SOPs for filling out medical record documents.